Law status of journalists and bloggers in the newest information legislation of Russian Federation (Proceedings of Southern Federal University. Philology, 2015)
The author carries out a comparative analysis of Russian national rights and responsibilities of journalists and bloggers, distinguishes fundamental differences in the legal status of the subject of information relations, determines the trend of development of the Russian legislation activity regulation of participants of information relations in the Russian segment of the Internet. On August 1, 2014 the Law on bloggers entered into force that, on the one hand fixed the differences between journalism as a profession and the blogosphere as a kind of social activity. On the other hand, at the legislative level it has solved the problem of the responsible attitude to bloggers - often influential and popular sources of information - to the broadcasting of messages. It is obvious that in Russian Federation it is being actively formed a system of legal regulation of information relations on the Internet, existed for many years legal gaps in this area are gradually disappearing.Keywords: law bloggers, media law, journalists, online media, legal status of journalists, legal status of bloggers, anonymous, responsibility, media, public communication.Kapustina Anna Georgievna - candidate of linguistics, professor assistant of theory of journalism dpt., Southern Federal University, Institute of linguistics, journalism and cross-cultural communication. E-mail: anna_ kapustina@mail.ru